Saccharomyces cerevisiae and its industrial applications - Maria Parapouli; Anastasios Vasileiadis; Amalia-Sofia Afendra; Efstathios Hatziloukas (AIMS Microbiology, 2020)
Saccharomyces cerevisiae is the best studied eukaryote and a valuable tool for most aspects of basic research on eukaryotic organisms. This is due to its unicellular nature, which often simplifies matters, offering the combination of the facts that nearly all biological functions found in eukaryotes are also present and well conserved in S. cerevisiae. In addition, it is also easily amenable to genetic manipulation. Moreover, unlike other model organisms, S. cerevisiae is concomitantly of great importance for various biotechnological applications, some of which date back to several thousands of years. S. cerevisiae’s biotechnological usefulness resides in its unique biological characteristics, i.e., its fermentation capacity, accompanied by the production of alcohol and CO2 and its resilience to adverse conditions of osmolarity and low pH. Among the most prominent applications involving the use of S. cerevisiae are the ones in food, beverage -especially wine- and biofuel production industries. This review focuses exactly on the function of S. cerevisiae in these applications, alone or in conjunction with other useful microorganisms involved in these processes. Furthermore, various aspects of the potential of the reservoir of wild, environmental, S. cerevisiae isolates are examined under the perspective of their use for such applications.